Prototipe Alat Kontrol Kualitas Air Dan Penebar Pakan Otomatis Pada Tambak Udang Berbasis Internet Of Things (IOT) - Indra Gunawan; Muhamad Sadali; Muhammad Wasil; Imam Fathurrahman (Fakultas Teknik Universitas Hamzanwadi, 2022)
Among all parameters of shrimp pond water quality, the degree of acidity (pH) and temperature play the most important role. Determination of the pH value is usually done by means of manual and periodic measurements by the operator using a pH meter, as well as the feeding process which is still done manually, which of course will occur in the process of feeding that is not. Therefore, the researchers designed a tool that can monitor the degree of acidity (pH) and temperature and make a shrimp pond feed spreader automatically using the internet. The use of connected intelligent software and systems to utilize data collected by sensors using the Internet of Things (IOT) technology approach and control automation using the blynk application platform. This research resulted in a prototype control system and monitoring data related to water temperature, pH content and control of fish feed automatically according to a predetermined time schedule.